Is Gratitude Associated With Suicidal Ideation in Veterans With Mental Illness and Student Veterans With PTSD Symptoms?. Issue 1 (January 2022) - Umucu, Emre; Lo, Chu-Ling; Lee, Beatrice; Vargas-Medrano, Javier; Diaz-Pacheco, Valeria; Misra, Kiran; Martin, Sarah L.; Thompson, Peter M.; Gadad, Bharathi S.
Abstract : Abstract: The present study is aimed to identify the effect of gratitude as an adaptive regulating mechanism from suicidal ideation (SI) for veterans with mental illness (study 1) and student veterans with posttraumatic stress disorder (PTSD) symptoms (study 2) in the United States. Descriptive statistics and regression analyses were used to examine sociodemographic characteristics and relationships between gratitude and SI. Our study 1 consisted of 156 veterans with mental illness. The mean age for study 1 was 37.85. Our study 2 consisted of 232 student veterans with PTSD symptoms. The mean age for study 2 was 28.43. Higher gratitude scores in study 1 and study 2 were significantly associated with lower SI scores after adjusting for demographics and depression. This study partially supports the association between gratitude and SI in veterans with mental illness. Based on the results from this study, gratitude interventions may be effective in reducing SI when working with veterans with mental illness.